Acute promyelocytic leukemia presenting as isolated femoral granulocytic sarcoma - Ayşe Şimşek; Hüseyin Tokgöz; Ümran Çalışkan (The Turkish Journal of Pediatrics)
Background. Granulocytic sarcoma (GS), or myeloid sarcoma or chloroma, is a tumoral mass containing myeloblasts and immature granulocytes in an anatomic site other than the bone marrow. GS is very rare in children with acute promyelocytic leukemia (APL). This case report presents a rare case of GS manifesting as a solitary bone mass.